2021
DOI: 10.1101/2021.08.02.454693
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional specialization of monocot DCL3 and DCL5 proteins through the evolution of the PAZ domain

Abstract: Monocot DICER-LIKE3 (DCL3) and DCL5 produce distinct 24-nt heterochromatic small interfering RNAs (hc-siRNAs) and phased secondary siRNAs (phasiRNAs). The former small RNAs are linked to plant heterochromatin, and the latter to reproductive processes. It is assumed that these DCLs evolved from an ancient "eudicot-type" DCL3 ancestor, which may have produced both types of siRNAs. However, how functional differentiation was achieved after gene duplication remains elusive. Here, we find that monocot DCL3 and DCL5… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The pre- miRNA 5′ phosphate is held in a pocket formed by the side chains of Arg1200 and Arg1207 and by the backbone amide groups of Ala1199 and Arg1200. This recognition mechanism contrasts that of plant DCL3, in which the phosphate binds a wider pocket formed by lysine side chains (Figure S5B and S5C) (Wang et al, 2021; Chen et al, 2022).…”
Section: Resultsmentioning
confidence: 75%
“…The pre- miRNA 5′ phosphate is held in a pocket formed by the side chains of Arg1200 and Arg1207 and by the backbone amide groups of Ala1199 and Arg1200. This recognition mechanism contrasts that of plant DCL3, in which the phosphate binds a wider pocket formed by lysine side chains (Figure S5B and S5C) (Wang et al, 2021; Chen et al, 2022).…”
Section: Resultsmentioning
confidence: 75%
“…Previous reports showed that DCL3 prefers to cleave dsRNA precursors from the end with 5′ A and/or unstable sequence (2325). Thus, we cannot exclude the possibility that the siRNAs with the 5′ A and the thermodynamically unstable ends are enriched at the DCL3-mediated cleavage steps but not at the loading step.…”
Section: Resultsmentioning
confidence: 99%
“…Sequencing of total small RNAs in plant cells showed that about 60% of 24-nt siRNAs have a 5′ A (18). This enrichment of 24A siRNAs can be explained by the biased selection of transcription start site (TSS) by Pol IV and the substrate specificity of DCL3: Pol IV TSSs exhibit preference for A or G at the +1 position (21), and DCL3 prefers to cleave dsRNA precursors from the end with 5′ A and/or unstable terminus (22)(23)(24)(25). On the other hand, sequencing of small RNAs loaded into AGO4/6 showed a slightly higher percentage of 24A siRNAs than total small RNAs (18), suggesting that 24A siRNAs are further enriched in the loading step.…”
Section: Introductionmentioning
confidence: 99%